We See This By The Father-Filial Responsibility - Emine Er (Muhammed Yıldız, 2019)
The inability of the adult person to be completely out of the parent's control should not be considered as an indicator of pathological dependence. The fact that a healthy adult individual is not able to fully comprehend his or her parent's authority is that he is aware that the adult individual is now autonomous and can help him take important decisions. The children also expresses gratitude towards his parents when he acknowledges that his parents have done for him and helped him to be who he is. This causes the children to feel a sense of love and gratitude towards his parents. Filial responsibility is examined with the perspective of parent and child. This concept represents that responsibility of children towards parent. Also, it includes that expectation of parent from their children. There are a lot of comprehension about filial responsibility. In this study, concept of filial responsibility is examined particularly and contributed to the literature.